A CRITICAL DISCOURSE ANALYSIS OF PRESIDENT BOLA AHMED TINUBU’S DEMOCRACY DAY SPEECH, JUNE 12, 2025 - BALA , Victoria; KEFAS , Jesimiel (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study critically examines President Bola Ahmed Tinubu’s 2025 Democracy Day speech through the lens of Critical Discourse Analysis (CDA), with the objective of uncovering the linguistic strategies employed to construct political legitimacy, promote national unity, and frame economic reforms. The study also aims to explore how the speech manipulates historical memory and rhetorical devices to mask underlying socio-political contradictions. The central problem addressed is the gap between political rhetoric and the lived experiences of citizens in a context marked by inequality, contested democracy, and socio-economic hardship. Drawing on Norman Fairclough’s three-dimensional model of CDA textual analysis, discursive practice, and socio-cultural context the analysis reveals a complex interplay between inclusive language, historical intertextuality, euphemistic expressions, and reformist lexical fields. Key findings show that the speech deploys inclusive pronouns like “we” and “our” to create a false sense of national cohesion, while references to democratic icons such as MKO Abiola are used to legitimize the current administration by linking it to Nigeria’s democratic past. Euphemistic language downplays the negative impacts of controversial policies like fuel subsidy removal, while reformist vocabulary constructs a visionary leadership persona. These discursive strategies obscure social exclusion, suppress dissent, and reinforce dominant power structures. The study concludes that Tinubu’s speech exemplifies how political discourse in Nigeria functions as an instrument of ideological control. It calls for increased critical engagement with political texts to foster accountability, transparency, and a more participatory democratic culture.